Combined Blunt Splenic Injury in Adults: Modern Approach to Diagnosis and Treatment - V. V. Aleksandrov; S. S. Maskin; V. V. Matyukhin (Неотложная медицинская помощь, 2021)
Background. The high frequency of injuries of the spleen, as well as its important immunocompetent role in the body, dictate the need to develop a standardized approach to the diagnosis and treatment of this category of patients.Aim. Standardization of the treatment and diagnostic approach for combined blunt splenic injury to improve treatment results.Material and methods. The analysis of literary sources of Russian and foreign authors on this issue.Results. The therapeutic and diagnostic algorithm was developed for combined blunt splenic injury based on the severity of the patient, and a detailed description of non-operative and damage control surgical treatment was given.Conclusion. The use of endovascular interventions in the treatment of splenic injuries, as well as their gradual treatment in conditions of severe polytrauma, helps to reduce mortality.